2015
DOI: 10.1111/ejn.12824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defeat stress on behavioral flexibility in males and females: modulation by the mu‐opioid receptor

Abstract: Behavioral flexibility is a component of executive functioning that allows individuals to adapt to changing environmental conditions. Independent lines of research indicate that the mu opioid receptor (MOR) is an important mediator of behavioral flexibility and responses to psychosocial stress. The current study bridges these two lines of research and tests the extent to which social defeat and MOR affect behavioral flexibility and whether sex moderates these effects in California mice (Peromyscus californicus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 60 publications
3
61
0
1
Order By: Relevance
“…We also expected that sex would moderate stress effects on cognitive flexibility, given some evidence suggesting stress impairs cognitive flexibility more in males than females (Laredo et al, 2015). Although the effect was in the expected direction, with a greater proportion of males descriptively associated with a greater impairment, percentage male participants did not emerge as a significant moderator of stress effects on cognitive flexibility, B = −.009, t (1.0)= −1.96, p =.299.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also expected that sex would moderate stress effects on cognitive flexibility, given some evidence suggesting stress impairs cognitive flexibility more in males than females (Laredo et al, 2015). Although the effect was in the expected direction, with a greater proportion of males descriptively associated with a greater impairment, percentage male participants did not emerge as a significant moderator of stress effects on cognitive flexibility, B = −.009, t (1.0)= −1.96, p =.299.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the few studies of stress effects on cognitive flexibility are relatively consistent in showing an impairment in cognitive flexibility following stress (e.g., Alexander et al, 2007; Laredo et al, 2015; Plessow et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The damaged sections were distributed across all four groups. On each section we also measured a nearby white matter tract that did not show receptor binding and subtracted this from the measurements for the area of interest to account for background (Inoue et al, 2013; Laredo et al, 2015). There was no difference in signal in these regions and sections used to control for non-specific binding.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research with both humans (Alexander et al, 2007; Plessow et al, 2011) and rodents (Laredo et al, 2015) has suggested that stress may impair cognitive flexibility—that is, the ability to flexibly switch between thoughts or rules in a goal-directed manner. However, when studying effects of stress, it is important to examine potential sex differences, given the dramatically different effects stress can have on males and females (Trainor et al, 2013); stress should not be presumed to influence males and females similarly (Cahill, 2012; Felmingham et al, 2012; Schoofs et al, 2013; Zoladz et al, 2013).…”
mentioning
confidence: 99%